Robust tori in a double-waved Hamiltonian model - Martins, C. G. L. [UNESP]; Marcus, F. A.; Caldas, I. L.; Egydio de Carvalho, R. [UNESP] (Elsevier B.V., 2010)
A Hamiltonian system perturbed by two waves with particular wave numbers can present robust tori, which are barriers created by the vanishing of the perturbed Hamiltonian at some defined positions. When robust tori exist, any trajectory in phase space passing close to them is blocked by emergent invariant curves that prevent the chaotic transport. Our results indicate that the considered particular solution for the two waves Hamiltonian model shows plenty of robust tori blocking radial transport. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Robust tori; Transport barriers; Chaos; Non-linear waves; Hamiltonian system